3(2a+1)-4=11

Simple and best practice solution for 3(2a+1)-4=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2a+1)-4=11 equation:


Simplifying
3(2a + 1) + -4 = 11

Reorder the terms:
3(1 + 2a) + -4 = 11
(1 * 3 + 2a * 3) + -4 = 11
(3 + 6a) + -4 = 11

Reorder the terms:
3 + -4 + 6a = 11

Combine like terms: 3 + -4 = -1
-1 + 6a = 11

Solving
-1 + 6a = 11

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 6a = 11 + 1

Combine like terms: -1 + 1 = 0
0 + 6a = 11 + 1
6a = 11 + 1

Combine like terms: 11 + 1 = 12
6a = 12

Divide each side by '6'.
a = 2

Simplifying
a = 2

See similar equations:

| 9v^2=-30v-25 | | 6x-5x=+1 | | 6w-14-9w=-5 | | 5-3*-1= | | 12y-3y+7=88 | | 8x^2+3x-7=0 | | 22p+11= | | 8(y+3)=2(2y+4) | | 4w^2+5=-21w | | 2(3)-5y=13 | | 7y=20 | | 3(x-2)+4x=8 | | 3x-10-5+6x=12 | | 4(7x-2)-16x= | | 7u=2u^2-4 | | z^2-13z+18=0 | | 5x(x-23)=-37 | | 20=4(d+3) | | (7+2a)+3a= | | 2-5y=13 | | 4(-3)+6(-8)+(-3)(78)-7(-42)= | | 6+x-x^2=0 | | n-12=5n+4 | | .4b+1=-11 | | 5x(x-23)=37 | | p+3p+2P=180 | | 12x^3+58x^2+70x= | | 13+(3xx)=50 | | x-2+x+x+5=40 | | 3w^2-11w=-6 | | 5m+2m-42=14 | | 0.3(3y-12)=6-2(y-1) |

Equations solver categories